Features of the application of cognitive systems analysis in the creation of information training systems for energy universities - Nikolay N. Tsibov; Jaloliddin T. Galbaev; Buboaisha B. Bekjanova; Askarbek K. Karmyshakov; Anvar G. Saidkhodjayev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: Despite the rapid development of information training systems with artificial intelligence, the problem of didactic efficiency of their application in technical universities has not yet been solved. Therefore, an urgent task is the analysis and development of methods for improving the didactic efficiency and quality of the educational process in technical universities using information-training systems. The purpose of this work is to improve the didactic efficiency of designing and applying cognitive automated training systems for power engineering universities. Methods. Due to the nonlinearity and unpredictability of the educational process, the main approaches in the research were cognitive-systemic, structural, expert, retrospective, factorial, statistical, correlation, situational, PEST analysis and SWOT analysis. Results. This paper presents a method for improving the didactic efficiency of using information-training systems by including elements of cognitive system analysis with feedback in the algorithm of functioning of training electronic devices. The feedback of information training tools includes new cognitive qualities of the student and models of virtual electronic devices of varying complexity, which are offered to the student for design. In order to develop new cognitive qualities in the learning process, based on the results of each stage of control testing of personal characteristics, the student, according to the method of A.V. Krutikov, participates in psychocorrectional work to eliminate irrational negative attitudes caused by the influence of the superego. Such negative attitudes are the cause of the manifestation of negative forms of response to the influence of society. Moreover, the presence of negative attitudes in the mind of a person significantly reduces cognitive abilities for creative activity.